1047. Asymptomatic SARS-CoV-2 Infections, BNT162b2 mRNA COVID 19 Vaccine-Related Symptoms, and Correlates of Immunity in Post-Vaccination Breakthrough Infections in the Prospective Assessment of SARS-CoV-2 Seroconversion (PASS) Study. (15th December 2022) - Goguet, Emilie; Weiss, Carol D; Olsen, Cara; Powers, John H; Coggins, Si'Ana A; Tribble, David; Davies, Julian; Illinik, Luca; Lusvarghi, Sabrina; Edwards, Margaret Sanchez; Jackson-Thompson, Belinda; Hollis-Perry, Monique; et al.
Abstract: Background: We sought to determine the frequency of asymptomatic SARS-CoV-2 infections, the BNT162b2 mRNA COVID 19 vaccine-related symptoms, and the correlates of immunity in post-vaccination breakthrough infections in a prospective cohort of healthcare workers. Methods: We have been conducting a single-center, observational cohort study of healthcare workers. 271 participants were enrolled since August 25, 2020. Testing for SARS-CoV-2 spike (S)-specific IgG antibodies is conducted using a microsphere-based multiplex immunoassay interpolated against an internal standard curve for binding antibody (bAb) units (BAU) and has been performed on serum samples collected at monthly visits between September 2020 to August of 2021, and quarterly since then. Neutralizing antibody titers against wild-type (WT) virus are determined by microneutralization assays and against Delta and Omicron variants by lentiviral pseudovirus neutralization assays. For the first 6 months, participants completed a symptoms questionnaire every day they had any symptoms. Results: 12 participants were diagnosed with SARS-CoV-2, with at least mild symptoms. Of 206 participants evaluated for adverse effects after 1st and 2nd vaccine doses, no relationship was observed between vaccine-associated symptom scores and antibody titers 1 month after the 2nd dose. Longitudinal studies demonstrate that anti-S IgG bAbs decrease from a geometric mean (GM) of 1929 BAU/mL at 1 month post-vaccination to a GM of 442 BAU/mL at 6 months post-vaccination ( P < 0.001, n=187), and that boosting increases S-specific IgG BAU. While only 5 of 39 participants had detectable anti-Omicron neutralizing activity 1 month after 2 vaccinations, booster vaccination resulted in detectable neutralizing activity for all participants. Conclusion: Asymptomatic infection is likely rare, that there is no relationship between vaccine-associated symptom severity and antibody titers 1 month after the 2nd vaccination, and that booster results in better protection against the Omicron variant. Ongoing studies are evaluating serological and cellular immune responses immediately prior to 38 breakthrough infections in an attempt to identify immune correlates of protection and will be reported at the conference. Disclosures: John H. Powers, III, MD, Arrevus: Advisor/Consultant|Eicos: Advisor/Consultant|Evofem: Advisor/Consultant|Eyecheck: Advisor/Consultant|Gilead: Advisor/Consultant|GlaxoSmithKline: Advisor/Consultant|OPKO: Advisor/Consultant|Resolve: Advisor/Consultant|Romark: Advisor/Consultant|SpineBioPharma: Advisor/Consultant|UTIlity: Advisor/Consultant|Vir: Advisor/Consultant David Tribble, MD, DrPH, Astra Zeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response Simon Pollett, MBBS, Astra Zeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response Timothy Burgess, MD, MPH, AstraZeneca: The HJF, in support of the USU IDCRP, was funded to conduct or augment unrelated Phase III Mab and vaccine trials as part of US Govt. COVID19 response.